Análise proteômica quantitativa de folhas, raízes e sementes de pinhão manso (Jatropha curcas L.) com teores contrastantes de ésteres de forbol - Farias, Andreza Raquel Barbosa de (2019)
Jatropha curcas L. is worth mentioning among the oleaginous species potential for the production of biofuels. The plant presents high oil content in its seeds, and the residue generated from the extraction of the oil, its pie, has characteristics that can increase the economic value of the crop. However, the pie use is limited due to toxic compounds, phorbol esters (PE). Although the toxicity and its disadvantages are well defined, the breeding of the species in order to reduce these compounds is still not efficient due to the lack of information about its biosynthesis. This work aimed at the proteomic study of endosperm, leafes and roots of jatropha, of two accessions with contrasting levels of PE, in order to identify proteins involved in the biosynthesis of such compounds and establish the tissue where it is synthesized. For this purpose, endosperm, leafs and roots of physic nut had their proteins extracted in pyridine / SDS buffer, underwent enzymatic trypsin hydrolysis, and the peptides obtained after the digestion were submitted to quantitative analysis by mass spectrometry using isobaric labeling with the iTRAQ reagent as well as free labeling strategies. Proteomic analysis of the three tissues resulted in the identification of a total of 5068 proteins. Of these, only 283 are shared between the three tissues, corresponding to 5.6% of the total identifications; 115 proteins are endosperm exclusive, 403 leaf exclusive and 3091 proteins appeared exclusively in roots, considering the parameters established in this study. Metabolic pathways of interest were analyzed, liposome biosynthesis in endosperm revealed proteins such as oleosins and lipases in both accesses, and although some oil storage related proteins were only identified in the highcontent access of phorbol esters, the correlation between toxicity and oil production can not be well established without additional testing. In the leafes the proteins related to protein biosynthesis were the most abundant, followed by those related to photosynthesis, with emphasis on the high content of phorbol esters. When the synthesis of terpenes was verified, most of the identified proteins were located in the jatropha roots, among them we identified proteins such as geranil geranyl diphosphate synthase and the casbene synthase (CS), both involved in the biosynthesis of diterpene precursors, emphasizing that the CS has not been verified in proteomic analyzes in this species until the moment. Also, in the roots, terpene transporters were also identified. The results obtained in this study suggest that the phorbol esters, although accumulated in jatropha seeds, are synthesized in their roots and transported to the other parts of the plant. Therefore, these results serve as subsidies for further studies, aimed at reducing the toxic components in the crop, which guarantees the best use of its potential.